Mass transfer and solubility of CO and H-2 in ionic liquid. case of [Bmim][PF6] with gas-inducing stirrer reactor - Sharma, Amit; Julcour, Carine; Kelkar, Ashutosh A.; Deshpande, Raj Madhukar; Delmas, Henri (Industrial & Engineering Chemistry Research, 2009)
Since the past decade, ionic liquids have gained significant importance as alternative solvents for catalysis applications. Many of the reactions evaluated in ionic liquids employ gases as substrates, and therefore it is important to know their solubility and mass transfer characteristics. This work reports for the first time both the solubility and volumetric gas-liquid mass transfer coefficient k(La) for hydrogen and carbon monoxide in 1-n-butyl-3-methylimidazolium hexafluorophosphate ([Bmim][PF6]) at three temperatures (293, 323, and 373 K) in relevance to hydroformylation reaction. The experimental data on the volumetric gas-liquid mass transfer coefficient are described by a dimensionless correlation for the bench-scale stirred tanks with gas-inducing impeller. k(La) values have also been evaluated for different [Bmim][PF6]-decane emulsions at 373 K.

Hydroformylation of 1-octene using [Bmim][PF6]-decane biphasic media and rhodium complex catalyst: thermodynamic properties and kinetic study - Sharma, Amit; Lebigue, Carine Julcour; Deshpande, Raj Madhukar; Kelkar, Ashutosh A.; Delmas, Henri (Industrial & Engineering Chemistry Research, 2010)
A chemical reaction engineering approach is reported to investigate the biphasic hydroformylation of I-octene using [bmim][PF6] ionic liquid. It is based both on a process parameter investigation (temperature, concentrations, and pressures) and a thermodynamic study of the reaction medium (gas liquid and liquid liquid equilibria). Initial rate data show complex behavior with respect to operating parameters and are best described by a rate equation based on a mechanistic model. Complete reaction scheme including isomerization is then modeled accounting from the time dependent concentration of the organic substrates measured in organic phase and recalculated in ionic liquid phase from liquid liquid equilibria.

Ultrasound promoted efficient and green protocol for the expeditious synthesis of 1, 4 disubstituted 1, 2, 3-triazoles using Cu(II) doped clay as catalyst - Dar, Bashir Ahmad; Bhowmik, Amrita; Sharma, Amit; Sharma, Parduman R.; Lazar, Anish; Singh, A. P.; Sharma, Meena; Singh, Baldev (Applied Clay Science, 2013)
Cu(II) doped clay catalyst has been prepared by an easy technique from inexpensive starting materials and investigated for the one pot synthesis of 1, 4-disubstituted 1, 2, 3-triazoles via Huisgen [3 + 2] cycloaddition under ultrasonic irradiation at room temperature. The catalyst is highly active, selective, and stable and can be reused several times. The prepared catalyst has been characterized by XRD, BET-SA, H-2-TPR, SEM and XPS techniques. This transformation is fast, efficient and does not require nitrogen atmosphere or anoxic conditions and additive. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Catalyst support; Copper catalyst; Crystallization; selectivity; Sustainability

Specific stereoisomeric conformations determine the drug potency of cladosporin scaffold against malarial parasite - Das, Pronay; Babbar, Palak; Malhotra, Nipun; Sharma, Manmohan; Jachak, Goraknath R.; Gonnade, Rajesh G.; Shanmugam, Dhanasekaran; Harlos, Karl; Yogavel, Manickam; Sharma, Amit; Reddy, D. Srinivasa (Journal of Medicinal Chemistry, 2018)
The dependence of drug potency on diastereomeric configurations is a key facet. Using a novel general divergent synthetic route for a three-chiral center antimalarial natural product cladosporin, we built its complete library of stereoisomers (cladologs) and assessed their inhibitory potential using parasite-, enzyme-, and structure-based assays. We show that potency is manifest via tetrahyropyran ring conformations that are housed in the ribose binding pocket of parasite lysyl tRNA synthetase (KRS). Strikingly, drug potency between top and worst enantiomers varied 500-fold, and structures of KRS-cladolog complexes reveal that alterations at C3 and C10 are detrimental to drug potency whereas changes at C3 are sensed by rotameric flipping of glutamate 332. Given that scores of antimalarial and anti-infective drugs contain chiral centers, this work provides a new foundation for focusing on inhibitor stereochemistry as a facet of antimicrobial drug development.

Design, synthesis, and structural analysis of cladosporin-based inhibitors of malaria parasites - Babbar, Palak; Das, Pronay; Manickam, Yogavel; Mankad, Yash; Yadav, Swati; Parvez, Suhel; Sharma, Amit; Reddy, Srinivasa (ACS Infectious Diseases, 2021)
Here we have described a systematic structure activity relationship (SAR) of a set of compounds inspired from cladosporin, a tool compound that targets parasite (Plasmodium falciparum) lysyl tRNA synthetase (KRS). Four sets of analogues, synthesized based on point changes in the chemical scaffold of cladosporin and other logical modifications and hybridizations, were assessed using high throughput enzymatic and parasitic assays along with in vitro pharmacokinetics. Co-crystallization of the most potent compound in our series (CL-2) with PfKRS revealed its structural basis of enzymatic binding and potency. Further, we report that CL-2 has performed better than cladosporin in terms of metabolic stability. It thus represents a new lead for further optimization toward the development of antimalarial drugs. Collectively, along with a lead compound, the series offers insights on how even the slightest chemical modification might play an important role in enhancing or decreasing the potency of a chemical scaffold.

Profiling of metabolic alterations in mice infected with malaria parasites via high-resolution metabolomics - Chhibber-Goel, Jyoti; Shukla, Anurag; Shanmugam, Dhanasekaran; Sharma, Amit (Molecular and Biochemical Parasitology, 2022)
Background: Malaria infection can result in distinct clinical outcomes from asymptomatic to severe. The association between patho-physiological changes and molecular changes in the host, and their correlation with severity of malaria progression is not fully understood. Methods: In this study, we addressed mass spectrometry-based temporal profiling of serum metabolite levels from mice infected with Plasmodium berhgei (strain ANKA). Results: We show global perturbations and identify changes in specific metabolites in correlation with disease progression. While metabolome-wide changes were apparent in late-stage malaria, a subset of metabolites exhibited highly correlated changes with disease progression. These metabolites changed early on following infection and either continued or maintained the change as mice developed severe disease. Some of these have the potential to be sentinel metabolites for severe malaria. Moreover, glycolytic metabolites, purine nucleotide precursors, tryptophan and its bioactive derivatives were many fold decreased in late-stage disease. Interestingly, uric acid, a metabolic waste reported to be elevated in severe human malaria, increased with disease progression, and subsequently appears to be detoxified into allantoin. This detoxification mechanism is absent in humans as they lack the enzyme uricase. Conclusions: We have identified candidate marker metabolites that may be of relevance in the context of human malaria.
Keywords: Host response; Infectious diseases; malaria; metabolite; Plasmodium

Targeted genomic surveillance unveils genetic variations linked to regional malaria drug resistance dynamics in India - Khilari, Ajinkya; Sharma, Shweta; Bajpai, Manali; Viswan, K. Anju; Chaturvedi, Rini; Mirdha, Bijay R.; Rahi, Manju; Sharma, Amit; Shanmugam, Dhanasekaran (Open Forum Infectious Diseases, 2026)
Background India has made substantial progress in reducing Plasmodium falciparum malaria cases and has set a target to eliminate malaria by 2030. Although artemisinin-based combination therapy (ACT) treatment remains effective, tracking regional differences in genetic variants associated with antimalarial resistance is required for effective drug policy implementation.Methods We analyzed 238 P. falciparum clinical samples from 6 Indian states by sequencing 15 parasite genes associated with reduced drug effectiveness. The method involved nanopore sequencing of target gene amplicons derived from dried blood spots using a highly-sensitive PfMDR15 surveillance panel.Results India's historical policy of artesunate-sulfadoxine-pyrimethamine in central India and artemether-lumefantrine in the Northeast has shaped contrasting resistance profiles. In the Northeast, chloroquine resistance persisted at high frequency (Pfcrt K76T and CVIET haplotype; Pfaat1 S258L), alongside quintuple and sextuple Pfdhfr-Pfdhps haplotypes conferring complete sulfadoxine-pyrimethamine resistance. Central India showed variable chloroquine resistance (parasites largely retained wild-type Pfcrt) and emerging lumefantrine tolerance (Pfmdr1 Y184F, Pfaat1 S258L). Interestingly, Delhi (Central India) parasites resembled profiles from the distant Northeast, which borders South East Asia. The detection of Pfaat1 S258L, previously reported only from Africa and associated with reduced lumefantrine susceptibility, suggests convergent evolution under ACT partner-drug pressure. No WHO-validated Pfk13 artemisinin resistance mutations were detected, supporting continued efficacy of ACT.Conclusions India's resistance landscape is fragmented, with signals of expanding lumefantrine tolerance and importation or evolution of globally relevant mutations. These findings highlight the importance of integrating molecular genomic surveillance into malaria control policy to monitor and protect ACT effectiveness and advance malaria elimination. Monitoring of drug resistance associated mutations in P. falciparum parasites is critical for effective drug treatment. We have demonstrated the use of a scalable genomic surveillance protocol for tracking drug resistance linked mutations in parasite genes from clinical isolates in India. The study suggests extensive regional diversity in antimalarial resistance profiles and provides the first hint of possible emergence of lumefantrine tolerance in India.
Keywords: drug resistance; malaria; Oxford nanopore; P. falciparum; pfMDR15